The Mediating Effect of Recovery Factors on Alcohol Addiction Recovery Interventions and Perceived Sobriety in the selected Hospital and Rehabilitation Centre: A cross-sectional study. - Celestine Lindrio (Student's Journal of Health Research Africa, 2026)
Background: Mediating recovery factors provide a very clear approach to establishing relationships between variables. The method used was highly recommended as a flexible and statistically powerful approach to the establishment of treatment facilities to promote recovery from alcohol abuse and enhance sobriety. Methods: A cross-sectional design was used to conduct the study; the researcher used a convergent mixed method involving a sequential explanatory design. Collection and analysis of quantitative data were done, as well as analysis of qualitative data. Priority given to quantitative data. A sequential exploratory design was used, where qualitative data collection and analysis were followed by quantitative data collection and analysis. Priority given to qualitative study. Findings were integrated during the interpretation phase. Concurrent triangulation design where only one data collection phase was used. Results: Mediating recovery factors results in alcohol addiction recovery interventions and perceived sobriety revealed a weak positive relationship between the level of alcohol addiction recovery interventions and perceived sobriety (r = .131, p = 0.112). This relationship is statistically significant with a p-value of 0.112. Therefore, the stated null hypothesis was rejected, meaning that there is an influence of alcohol greater than a 0.05 level of significance on perceived sobriety. Results showed that there is a positive but significant relationship between perceived sobriety and alcohol addiction recovery interventions (r = 0.169, p = 0.001). The findings suggest that the application of alcohol addiction recovery interventions results in perceived sobriety. Hypothesis results showed that recovery factors have a statistically significant effect on alcohol addiction recovery interventions and perceived sobriety. Conclusion: The mediating effect has a significant relationship between alcohol addiction recovery interventions and perceived sobriety. Recommendation: Ministry of Health and District Health Officers, through the Mental Health hospital in charge, consider the adoption of the ISCAR model to be used in treatment facilities.